DETERMINAN GANGGUAN MENTAL EMOSIONAL DI MASA PANDEMI COVID-19 PADA REMAJA SMA DI KOTA DEPOK 2021 - Angsoka Rahingrat (2022)
Mental-emotional disorder is a manifestation of abnormal cognition, emotion, and behavior,- influenced by individual, social, and environmental factors. During the Covid-19 pandemic, there was an increase in mental-emotional disorder, especially among adolescent. This study was conducted to find the determinants of emotional mental disorder during the Covid-19 pandemic in senior high school students in Depok City. This study used cross-sectional design with population all senior high scholl students in Depok City and cluster sampling to 3 senior high schools in Depok using the cluster sampling method. The study was conducted from September 2021 to January 2022. Data collection to 254 respondents was conducted in December 2021 using online questionnaire. The dependent variable of the study was the incidence of mental-emotional disorder. Independent variables in this study are age, sex, addiction to social media, cyberbullying, academic burnout, pandemic fatigue, and social support. Data analysed with univariate, bivariate, and multivariate analysis. Based on the results from bivariate analysis, is it known that sex, addiction to social media, cyberbullying actors, academic burnout, pandemic fatigue, and low social support affect mental-emotional disorder. The multivariate test show that the most influental determinant of mental-emotional disorder was addiction to social media (POR 9.581, 95% CI 2.906-31.588). Senior high school students in addiction to social media tend to be 9,581 times higher risk of experiencing mental-emotional disorder. It is expected that senior high school students in Depok City pay attention to the intensity of using social media so that there will be no addiction adverse impacts on mental health. Schools in Depok City should coordinate with students' parents in increasing the supervision of social media use. The result of this study should be considered by Depok City local government to formulate youth-friendly policies, as well as educating the public, especially adolescents about the importance of mental health.